Impact of Ageing on Curative Health Care Workforce : Country Report Denmark - Erika Schulz (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper shows the impact of demographic change on the demand for and supply of health care workforce in Denmark. As the need for health care services increases with age, the population ageing is expected to have a direct influence on the demand for health care and its workforce. The future supply of the health workforce is determined by the currently considerable portion of workforce that is approaching retirement age during the next 15 years. Based on the NEUJOBS demographic scenarios tough and friendly and age- and gender specific utilization rates the changes in the health workforce needed are calculated. Changes in labour supply and employment are shown using the results of the econometric model NEMESIS. In both demographic scenarios an increase in population size and an ageing of the population is expected. In 2025 every fifth persons will be at least 65 years old. In the tough scenario with constant fertility rates and a moderate increase in life expectancy the pure demographic effect will lead to an increase in the demand for health professionals by around 8 %. In the friendly scenario with an increase in fertility rates and a higher increase in life expectancy the demand for health workforce will increase by 13 %. The estimated increase in employment will meet the demand in the friendly scenario, while in the tough scenario a strengthening of the health workforce shortage is calculated.
Additional information: This publication was produced as part of the NEUJOBS project, funded by the European Commission through the 7th Framework Programme under contract no. 266833 (http://www.neujobs).; info:eu-repo/grantAgreement/EC/FP7/266833
Keywords: 330; Alternde Bevölkerung; Gesundheitsberufe; Pflegeberufe; Gesundheitswesen; Dänemark